Analyzing the Value Chain in Islamic Banking Financing: An Islamic Economic and Global Financial Perspective - Ali Akbar; Elsya Meida Arif; Vensy Vidya; Alfiana; Dipa Teruna Awaludin; Wahdi , Nirsetyo (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2025)
This research investigates and critically analyzes the financing value chain within Bank Syariah Indonesia. Employing a case study methodology, the study explores a specific phenomenon in depth through systematic interviews, direct observations, and document analysis to capture the case's contextual and structural intricacies. The selection of informants was carried out purposefully to ensure relevance to the research objectives, as the credibility and validity of qualitative findings largely depend on the suitability of participants. The informants comprised individuals holding strategic roles and possessing substantial insights into the studied context, specifically one leader and one staff member representing each relevant division. The study population encompasses Islamic banking institutions operating in Indonesia. The findings reveal that the problem formulation and data analysis regarding Value Chain Analysis under Sharia principles highlight several key aspects. The implementation of Value Chain Analysis integrated with Sharia-based frameworks aligns with Good Corporate Governance practices, grounded in five core principles essential to achieving sound governance standards.